Analisis Pembangunan Nasional Pemerintah Pusat dan Daerah Dalam Pembangunan Infrastruktur di Indonesia - Ferlita, Shinta; Saepudin, Eli Apud; Maharani, Putri Suci; Kurniawan, Irvan Pajar; Susilawati, Sindi; Al Fauzan, Riza Zidan (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Infrastructure development has become one of the main focuses of the Indonesian government in recent years. One of the main challenges is budget constraints. To overcome these budget limitations, the government needs to look for new sources of funding, such as through collaboration with the private sector. Another challenge is the inequality of infrastructure development. Infrastructure development in remote areas is still lagging behind compared to infrastructure development in urban areas. To overcome this, the government needs to prioritize infrastructure development in remote areas. Although there are several challenges, there are also several opportunities to improve infrastructure development in Indonesia. One of the opportunities that exists is increased investment from the private sector. The government needs to create a conducive investment climate so that private parties are interested in investing in infrastructure. Another opportunity is technological progress. New technology can be used to accelerate infrastructure development and improve infrastructure quality. Infrastructure development is one of the keys to encouraging economic growth and improving community welfare. The central and regional governments have made various efforts to improve infrastructure development in Indonesia. Although there are several challenges faced, there are also several opportunities to improve infrastructure development in Indonesia.